ANFIS MPPT with power management strategy to harvest reliable power from standalone PV systems to residential loads - Subbaraman Alagammal; Ramachandran Bhavani; Mohammed Muhaidheen (Institute of Advanced Engineering and Science, 2023)
In recent decades, the matching between the growing energy demand and generation is becoming the challenging task to the researcher’s leads for the development of standalone solar photo voltaic (SSPV) power system. The SSPV system is more suited for electrification of essential loads uses DC power as it offers high efficiency. This work aims to model and simulate SSPV with lead acid battery is used as a DC source. The proposed series shunt charge controller with power management strategy (PMS)is designed and modeled to control the power flow among SSPV, battery and the load. adaptive neuro fuzzy inference system (ANFIS) controller effectively regulates the output voltage by controlling duty ratio of the suitable converter for driving a DC load. A PMS is developed for selecting the operating mode of SSCC by sensing and regulating the battery voltage within 11.6-12.95 V. Here, the 250 Wp panel has been employed to charge a 12 V, 34 AH battery. The practicability of SSPVB system is verified under various loaded conditions using MATLAB/Simulink for a period of 24 hours. A simulation result proves that this SSPV Battery system is capable to electrify the essential loads in rural and isolated areas and also reduce the dependency of grid power.